(untitled) (Research, Society and Development, 2021)
The suspension of in-person activities in educational institutions, due to the restrictions imposed by COVID-19, it caused a readjustment of the Brazilian educational system. Given this scenario, this work presents the strategies adopted by the Federal Institute of Pará – Paragominas campus for the implementation of emergency remote learning. The study exposes the technological tools used for synchronous and asynchronous interactions and the creation of integration groups by curricular components to work in teaching and/or organizing teaching materials. Furthermore, it describes an experience report with integrating classes between the disciplines of Physical Education and Sociology. In this context, the Paragominas campus reconfigured the traditional teaching methodology with the use of digital media associated with integrated didactic-pedagogical actions, continuing the teaching activities of the year 2020.